Between Necessity and Delight - Negotiating Involved Fatherhood among Career Couples in Denmark. - Bach, Anna Sofie (Kvinder, Køn & Forskning, 2015)
Fathering practices are changing. Many fathers are no longer simply providers but are also active caregivers. While women’s entry into the labour market spurred a need for men to engage with the ‘second shift’, research has showed that men’s engagement with childcare does not necessarily imply an equal division of labour. By examining the construction of father’s identity in a context where traditional scripts for ‘doing family’ cannot (easily) be applied, this article discusses how necessity affects practices of involved fathering and the sharing of responsibilities. Based on qualitative interviews with 22 Danish men who are in relationships with so-called career women, the article argues that among this group of men, who in many ways appear as frontrunners of egalitarian family practices, fathers’ involvement is not only negotiated as a an emotional investment but also from a need to ‘make it work’. These fathers’ close relationships with their children and their parental independency is as much the result of the career orientation of the mothers as an expression of their having embraced the (Nordic) ideal of gender-neutral, symmetrical parenthood. Finally, in showing how intensive involvement and care-giving change men’s experience of fatherhood, the article contributes to the ongoing academic enquiry into what it means to be an involved father.